New genus and species of eriophyid mites (Acari, Eriophyidae) from Myrtaceae in Brazil, with notes on damages caused by Aculus pitangae Boczek & Davis - Flechtmann, Carlos H.w.; de Moraes, Gilberto J. (Zootaxa, 2003)
Surveys conducted on cultivated myrtaceous plants in southeast Brazil led to the discovery of a new genus and three new species of eriophyid mites. Diptilostatus Flechtmann, n. g., is described based on the type species Diptilostatus nudipalpus Flechtmann, n. sp., collected on Eugenia uniflora L. Calacarus kleithria Flechtmann, n. sp. is described from the same plant, while Aculus conspicillatus Flechtmann, n. sp. is described from Psidium guajava Raddi. Differently from what was mentioned in the original description of Aculus pitangae Boczek & Davis, A. pitangae was observed that it may distort and change the texture of leaves of E. uniflora, its host plant.